Assessing Change-Points in Surface Air Temperature Over Alaska - Khapalova, Elena A.; Jandhyala, Venkata K.; Fotopoulos, Stergios B.; Overland, James E. (Frontiers in Environmental Science, 2018)
An understanding of low frequency climatic variations is important for climatologists and planning by broader populations. This study applies recent advances in statistical change-point methodology to the variability of temperatures from seven stations in Alaska and the Pacific Decadal Oscillation (PDO) climate index. We allow for the presence of multiple change-points in any given data series and provide confidence intervals for the identified change-points. We analyze the multiple station data based on season and temperature means and extremes. Physical processes that correlate with specific identified temperature changes have been explored through geopotential height field maps and sea level pressure (SLP) maps. Predominantly, temperature and PDO shifts were observed during winter and spring in the 1940s and 1970s. However, as an anomaly, this study also identifies that changes in summer have occurred either in 60s or in the 80s, deviating substantively from the 40s and 70s changes that were observed during winter and spring. We also note that there is lack of clear low frequency cyclic variability in the northern North Pacific region.